Kratom use as more than a "self-treatment". (2nd November 2022) - Smith, Kirsten E.; Dunn, Kelly E.; Rogers, Jeffrey M.; Grundmann, Oliver; McCurdy, Christopher R.; Garcia-Romeu, Albert; Schriefer, Destiny; Swogger, Marc T.; Epstein, David H.
ABSTRACT: Background: Mitragyna speciosa (kratom) is increasingly used in the United States for its pharmacological effects. Kratom's relative novelty makes for a dynamic situation, such that use motivations are not firmly established and may be changing. Investigators and clinicians require frequent updates on kratom trends. Objectives: To assess the current state of kratom-use initiation, sourcing, motivations, preference, conceptualizations, and perceived stigma, using survey responses from current and former users. Methods: Between April-May 2021 we recontacted 289 respondents who reported lifetime kratom use (on an unrelated survey) to answer kratom-specific questions. Results: The sample (N=129) was majority female (51.9%) and white (71.9%). Most (69.0%) reported first trying kratom after 2015. Mean age of use initiation (29.9 years) was older than for other substances, including opioids. Kratom ranked as a preferred substance by 48.5%. The strongest drug association with past-year kratom use was vaped nicotine ( OR= 3.31, 95% CI 1.23-8.88). Use was less likely among those prescribed buprenorphine in the past year ( OR= 0.03, CI 0.01-0.28). Past-month cannabis use ( OR= 4.18, CI 1.80-9.72) had the strongest association with past-month kratom use. Over 40 use motivations were endorsed, many (but not all) supporting the "self-treatment" narrative of kratom use, including use as an opioid, alcohol, or stimulant substitute. Treatment shortfalls were associated with decisions to try kratom. Conclusions: Kratom use motivations are diversifying, with multiple factors driving use. As sales continue to increase, the public-health, clinical, and policy responses to kratom should be grounded in rigorous bench-to-bedside scientific research. Comprehensive study of kratom is currently lacking.